Influence of water and surfactant contamination on the mechanical and chemical properties of a silicone adhesive before and after curing. Issue 6 (26th April 2023) - Borges, C.S.P.; Brandão, R.; Akhavan-Safar, A.; Marques, E.A.S.; Carbas, R.J.C.; Ueffing, C.; Weißgraeber, P.; Schmid, F.; da Silva, L.F.M.
ABSTRACT: This work aims to analyze the mechanical and chemical effects that contaminants can have prior to curing of the silicone adhesive, if they are in the substrate or surrounding environment at adhesive application, as well as after curing when they appear during the service life of the joint. In this case, the contaminants are water and a surfactant present in detergents used to clean oils from aluminum surfaces. For this, 2%, 5%, and 10% of contaminant was added to the adhesive prior to curing and neat adhesive after curing was immersed in contaminant at different temperatures. For all cases, the effect on the mechanical properties was evaluated through bulk tensile tests, the effect on the chemical profile was evaluated using Fourier-transform infrared spectroscopy (FTIR) and the morphology of the materials was studied with scanning electron microscopy (SEM). The water immersion increased slightly the mechanical properties of the adhesive, which returned to their initial value upon redrying. However, high immersion temperatures introduce irreversible damage in the material. Water added prior to curing introduces voids in the adhesive, decreasing its strength. The surfactant added prior to curing changes the adhesive morphology, showing a variation in the C-H bond. These changes translate into a lower strength and stiffness of the mixture.